Clinical Determinants of Parkinson's Disease-associated Pain Using the King's Parkinson's Disease Pain Scale - Rodríguez-Violante, Mayela; Alvarado-Bolaños, Alonso; Cervantes-Arriaga, Amin; Martinez-Martin, Pablo; Rizos, Alexandra; Chaudhuri, K Ray (Movement disorders clinical practice (Hoboken, N.J.), 2017)
Pain is a frequent feature in Parkinson's disease (PD). Current knowledge on pain and its associated factors in PD has been obtained using nondisease-specific tools. Recently, the King's Parkinson's Disease Pain Scale (KPPS) was published as the first disease-specific scale. The aim of this study was to assess PD-associated pain and its main determinants using the KPPS. A cross-sectional study was carried out. Consecutive patients with PD were recruited from a movement disorders clinic. Clinical and demographical data were collected. The KPPS, the Movement Disorders Society Unified Parkinson's Disease Rating Scale, and the Non-Motor Symptoms Scale were used to assess all participants. In total, 314 patients were included. Overall, 88.6% of the sample reported at least 1 type of pain. The mean ± standard KPPS score was 18.8 ± 19.5. Factors associated with higher KPSS scores were female sex ( < 0.001), levodopa treatment ( < 0.001), the presence of depressed mood ( < 0.001), wearing off ( = 0.003), and dyskinesia ( = 0.005). Participants who had postural instability and gait difficulty motor subtypes had higher KPPS scores compared with those who had other subtypes. Multivariate regression analysis showed that only sex, motor subtype, depressed mood, and Non-Motor Symptoms Scale sleep/fatigue domain scores achieved statistical significance as determinants (all < 0.01). PD-associated pain is a frequent symptom that tends to increase in both frequency and severity as disease progresses. Risk factors for increased burden include female gender, postural instability and gait difficulty motor subtypes, mood alterations, and sleep/fatigue disturbances.